Stealing the network how to own an identity - Alder, Raven; Mullen, Timothy M.; Long, Johnny (Rockland, MA : Syngress ; [Sebastopol, CA] : Distributed by O'Reilly Media, 2005)
The first two books in this series Stealing the Network: How to Own the Box and Stealing the Network: How to Own a Continent have become classics in the Hacker and Infosec communities because of their chillingly realistic depictions of criminal hacking techniques. In this third installment, the all-star cast of authors tackle one of the fastest growing crimes in the world: Identity Theft. Now, the criminal hackers readers have grown to both love and hate try to cover their tracks and vanish into thin air "Stealing the Network: How to Own an Identity" is the 3rd book in the "Stealing" series, and continues in the tradition created by its predecessors by delivering real-world network attack methodologies and hacking techniques within a context of unique and original fictional accounts created by some of the world's leading security professionals and computer technologists. The seminal works in TechnoFiction, this "STN" collection yet again breaks new ground by casting light upon the mechanics and methods used by those lurking on the darker side of the Internet, engaging in the fastest growing crime in the world: Identity theft. Cast upon a backdrop of "Evasion," surviving characters from "How to Own a Continent" find themselves on the run, fleeing from both authority and adversary, now using their technical prowess in a way they never expected--to survive. * The first two books in the series were best-sellers and have established a cult following within the Hacker and Infosec communities * Identity theft is the fastest growing crime in the world, and financial loss from identity theft is expected to reach $2 trillion by the end of 2005 * All of the authors on the book are world renowned, highly visible information security experts who present at all of the top security conferences including Black Hat, DefCon, and RSA and write for the most popular magazines and Web sites including Information Security Magazine, and SecurityFocus.com. All of these outlets will be used to promote the book.
pt. 1 Evasion: Prologue from the diary of Robert Knoll, Senior / Ryan Russell ; In the beginning ... / Caezar as The Woman With No Name ; Sins of the father / Ryan Russell as Robert ; Saul on the run / Chris Hurley as Saul ; The seventh wave / Thor as Ryan ; Bl@ckToW3r / Brian Hatch as Glenn ; The Java SCript Cafβe / Raven Alder as Natasha ; Death by a thousand cuts / Johnny Long with Anthony Kokocinski ; A really gullible genius makes amends / Jay Beale as Flir ; Near miss / Tom Parker as Carlton ; There's something else / Johnny Long with Anthony Kokocinski ; Epilogue : The chase / Johnny Long -- pt. 2. Behind the scenes: The conversation / Jeff Moss as Tom ; Social insecurity / Thor.
Keywords: Identity theft -- Fiction; Computer crimes -- Fiction; Computer hackers -- Fiction; Computer security -- Fiction; Computer hackers -- Psychology -- Fiction; Identity theft; Computer crimes; Computer hackers; Computer security; Computer hackers -- Psychology; Short stories; Electronic books